2021
DOI: 10.1126/sciadv.abj5830
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterials direct functional B cell response in a material-specific manner

Abstract: B cells are an adaptive immune target of biomaterials development in vaccine research but, despite their role in wound healing, have not been extensively studied in regenerative medicine. To probe the role of B cells in biomaterial scaffold response, we evaluated the B cell response to biomaterial materials implanted in a muscle wound using a biological extracellular matrix (ECM), as a reference for a naturally derived material, and synthetic polyester polycaprolactone (PCL), as a reference for a synthetic mat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 74 publications
(104 reference statements)
0
20
0
Order By: Relevance
“…Our understanding of the nuanced cascade of events, the diversity and plasticity of relevant cell populations and the influence of material properties involved of the progression of the FBR has continued to evolve. Yet, recent advances on understanding the dynamic signaling of innate and adaptive immune cells and their crosstalk with stromal cells within implant sites has revealed that many aspects of the FBR remain unclear and merit further investigation (Sadtler et al, 2019;Wolf et al, 2019;Moore et al, 2021;Fernandez-Yague et al, 2022). As such, the FBR remains a significant challenge for many biomedical devices used in clinical applications, including the formation of foreign body granulomas within surgical meshes and tissue fillers that cause adhesions and pain, fibrous capsular contractures surrounding silicone breast implants and issues with reliability, noise and the constant need for recalibration for implantable glucose sensors (Rigla et al, 2018;Singh et al, 2018;Lemperle et al, 2020;Kuehlmann et al, 2021;Klinge et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our understanding of the nuanced cascade of events, the diversity and plasticity of relevant cell populations and the influence of material properties involved of the progression of the FBR has continued to evolve. Yet, recent advances on understanding the dynamic signaling of innate and adaptive immune cells and their crosstalk with stromal cells within implant sites has revealed that many aspects of the FBR remain unclear and merit further investigation (Sadtler et al, 2019;Wolf et al, 2019;Moore et al, 2021;Fernandez-Yague et al, 2022). As such, the FBR remains a significant challenge for many biomedical devices used in clinical applications, including the formation of foreign body granulomas within surgical meshes and tissue fillers that cause adhesions and pain, fibrous capsular contractures surrounding silicone breast implants and issues with reliability, noise and the constant need for recalibration for implantable glucose sensors (Rigla et al, 2018;Singh et al, 2018;Lemperle et al, 2020;Kuehlmann et al, 2021;Klinge et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The transition from the acute to chronic inflammation is accompanied by a shift in the cytokine profile to include cytokines generally associated with late/sustained inflammation, such as MCP-1, and Regulated upon Activation, Normal T Cell Expressed and Presumably Secreted (RANTES/CCL5), and with tissue regeneration and fibrosis, including transforming growth factor beta (TGF-β), plateletderived growth factor (PDGF) and IL-10 (Anderson et al, 2008;Melton et al, 2015;Zhao et al, 2016;Liu and Segura, 2020;Martin and Garcia, 2021). Macrophages and their crosstalk with fibroblasts are well established as central actors in the progression and severity of the FBR, while more recent studies have enriched our understanding of the roles of adaptive immune cells, including T cells and B cells, in the complex immune microenvironment surrounding a biomaterial implant during the later stages of chronic inflammation and peri-implant fibrosis (Anderson et al, 2008;Witherel et al, 2019;Moore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ECM materials induced mature B cells in lymph nodes and antigen presentation in the spleen, while the synthetic PCL implants prolonged B cell presence in the wound area. [76] In a nutshell, all these findings mentioned above provide a deeper understanding of immune micro-environment around biomaterials, which may offer insights into future immunomodulatory biomaterial design. [72] High-throughput sequencing techniques such as bulk tissue RNA sequencing (bulk RNA-seq), scRNA-seq and proteomics can provide massive information on the gene and protein expression profiles of tissue surrounding scaffolds.…”
Section: Recent Advances In Elucidating the Mechanisms Of Fbrmentioning
confidence: 99%
“…B cells appear to sense the mechanics of follicular dendritic cells in the lymph node germinal centre and the forces required to extract antigens from the surface of follicular dendritic cells as a way of promoting the preferential uptake of high-affinity antigens over low-affinity antigens from the environment 68 . A recent publication also reported that different biomaterial implants with essentially distinct mechanical properties affect the B cell response to muscle injury 70 . For instance, synthetic polyester implants induced certain B cell pathways including strengthening their presentation of antigens and expressing inflammation-related genes.…”
Section: Mechanotransduction In Immune Cellsmentioning
confidence: 99%